X as a Catalyst for Change: Mass Mobilization Through the #PeringatanDarurat Hashtag in Indonesia's Digital Democracy - Sidauruk, Eva Ronita; Azizah, Ratu Reszha; Fahrezi, Irgi Ahmad; Evandy, Marcello; Fatkhuri, Fatkhuri (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This research explores the complexities of mass mobilization through the hashtag #PeringatanDarurat in Indonesia's digital democracy, analyzing how social media transforms public participation in the contemporary democratization process. In the dynamic digital communication landscape, hashtags have evolved into strategic instruments for mobilizing collective awareness, shaping public opinion, and driving socio-political action. Through qualitative research with a constructivist approach, this comprehensive study will delve into the perspectives of X social media users, where hashtags serve as a communication medium capable of transcending traditional geographical and structural boundaries. The research methodology includes analyzing digital content by influencers, activists, and public figures who play a crucial role in issue dissemination and systematic observation of virtual interactions. The main focus of the research is to uncover the complex dynamics of how the hashtag #PeringatanDarurat shapes public narratives, creates spaces for democratic dialogue, and mobilizes the masses through social media platforms. This study aims to provide a deep understanding of the transformation of democratic practices in the digital era by showcasing the potential of social media in shaping social movements, raising critical awareness, and encouraging citizen participation. This research finds that the hashtag #PeringatanDarurat on social media X has become an effective tool for digital activism that mobilizes the public to reject the revision of the Regional Election Law. This movement demonstrates the power of mass autonomous communication in pushing back against policies, encouraging real action, and strengthening digital democracy in Indonesia.